Nuclear data measurements at the new NFS facility at GANIL - Gustavsson C. (2017)
The NFS (Neutrons For Science) facility is part of the SPRIAL 2 project at GANIL, Caen, France. The facility is currently under construction and the first beam is expected in early 2013. NFS will have a white neutron source covering the 1-40MeV energy range with a neutron flux higher than comparable facilities. A quasi-mono-energetic neutron beam will also be available. In these energy ranges, especially above 14MeV, there is a large demand for neutron-induced data for a wide range of applications involving dosimetry, medical therapy, single-event upsets in electronics and nuclear energy. Today, there are a few or no cross section data on reactions such as (n, fission), (n, xn), (n, p), (n, d) and (n, α). We propose to install experimental equipment for measuring neutron-induced light-charged particle production and fission relative to the H(n, p) cross section. Both the H(n, p) cross section and the fission cross section for 238 U are important reference cross sections used as standards for many other experiments. Nuclear data for certain key elements, such as closed shell nuclei, are also of relevance for the development of nuclear reaction models. Our primary intention is to measure charged particle production (protons, deuterons and alphas) from 12 C, 16 O, 28 Si and 56 Fe and neutron-induced fission cross sections from 238 U and 232 Th. © 2012 The Royal Swedish Academy of Sciences.